2010
DOI: 10.1016/j.mcna.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Otalgia

Abstract: Otalgia, pain in the ear, can be a consequence of otologic disease (primary or otogenic otalgia), or can arise from pathologic processes and structures other than the ear (secondary or referred otalgia). In children, ear disease is far and away the most common cause of otalgia, but in adults, secondary or referred otalgia is more common. Otalgia can be the only presenting symptom of several serious conditions, and its etiology should be fully explored. Unfortunately, its workup is complex and no simple algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 18 publications
3
30
0
6
Order By: Relevance
“…7 In our study the most common age of presentation was around 46-60 yrs of age and no cases were reported in children. This is consistent with findings of Neilan's et al 8 In study by Mohammad Hosein et al, the most common age of presentation was 21-35yrs. 7 In our study, 50.8% of the patients were women and 49.2% were men.…”
supporting
confidence: 92%
“…7 In our study the most common age of presentation was around 46-60 yrs of age and no cases were reported in children. This is consistent with findings of Neilan's et al 8 In study by Mohammad Hosein et al, the most common age of presentation was 21-35yrs. 7 In our study, 50.8% of the patients were women and 49.2% were men.…”
supporting
confidence: 92%
“…In a study by Jaber et al, examining patients presenting with otalgia, cervical pathology was the most common cause of referred otalgia, with TMJ dysfunction and dental pathology being the second and third most common diagnoses. TMJ disorders are a collection of musculoskeletal disorders affecting the joint and muscles of the jaw, with approximately 65% of patients with TMJ disorders complaining of otalgia . Pain is referred through the auriculotemporal nerve, via the mandibular division of the trigeminal .…”
Section: Discussionmentioning
confidence: 99%
“…This study did not identify any malignancies, but due to the fact that patients with otalgia with no known cause found on clinical examination were included, it may be that the likelihood of picking up such a patient was reduced, compounded by the relatively low number of patients studied. CT, rather than MRI, was used Correlation of age with abnormalities found on CT scans musculoskeletal disorders affecting the joint and muscles of the jaw, with approximately 65% of patients with TMJ disorders complaining of otalgia 5. Pain is referred through the auriculotemporal nerve, via the mandibular division of the trigeminal 4.…”
mentioning
confidence: 99%
“…Neilan's study also found that children suffer more from primary otalgia while more number of adults had referred otalgia which is consistent with our study. 4 But in study by Mohammad Hosain Taziki, Golestan Uni, Gorgan, Iraq, reffered otalgia were common in children. 5 We found that in our study commonest cause for referred otalgia is tonsillar lesions (29%) which is seen most commonly among the pediatric and early adulthood group and as a cause of bilateral referred otalgia followed by dental pathology (25.8%) including toothache having its highest incidence in more than 50 years age group and oral lesions of benign nature like oral ulceration and trauma is noted in 9.6% cases with maximum number of cases seen in second decade.…”
Section: Discussionmentioning
confidence: 99%